Reflexivity, methodology and contexts in participatory digital media research: making games with Latin American youth in London - Paula, Bruno de (Learning, Media and Technology, 2021)
In this paper, I intend to explore the role played by reflexivity in grounding a more critical perspective when designing, implementing and analysing participatory digital media research. To carry out this methodological reflection, I will present and discuss a recently concluded research project on young people’s game-making in an after-school programme targeting Latin American migrants in London/UK. I will pay special attention to how my subjectivities influenced planning, data generation and analysis of this programme, and to how context, lived experiences, curricular decisions and interpersonal relationships shaped the kinds of knowledge produced through this research. Findings emerging from this experience included relevant dissonances between curricular design/decisions and the use of participatory approaches in game-making, and the limitations of traditional analytical categories within the Social Sciences field (e.g., gender and intersectionality) to understanding subjectivities expressed through game-making. This study offers relevant insights into the place of reflexivity in research on digital media production by young people by highlighting its complexity and by calling for more critical and less homogenising approaches to this type of research.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Korean Soap Operas, Telenovelas and Sci-fi Conspiracies: A Game-making Experience with Latin American Youth in London - Paula, Bruno de (Digital Culture and Education, 2021)
This paper explores a game-making programme for 14 Latin American migrants aged 13-18 in London/UK, carried out between October/2017-January/2018, where I investigated the relationships between game conventions, platforms and personal preferences in the curation of fluid identities through game production. Participants presented varying levels of affinity with games linked both to access issues and to other specific elements (e.g. perception of games in contemporary culture, gender). Questionnaires, observations, unstructured/semistructured interviews and gaming archives were employed to explore this participatory initiative and data was analysed through Multimodal Sociosemiotics. Findings remarked how shared understandings about digital games can find their way into platforms and act as “cultural-technical gatekeepers”, supporting or hindering the engagement with game-making of those often perceived as outsiders to gaming culture. This gatekeeping happens when there are “creative dissonances” between, for example, personal preferences and platforms aligned to normative/mainstream genres. These dissonances, however, can end up fostering subversive designs, contravening gaming conventions and potentially challenging traditional gaming boundaries. This insight is relevant for understanding “cultural-technical constraints” and subversive/non-mainstream game-making, especially in relation to innovation and appropriation of game-making resources/strategies by non-mainstream groups.
Keywords: 1-Jeux vidéo; 1-TV; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Planet TV: A Global Television Reader - Parks, Lisa; Kumar, Shanti (NYU Press, 2003)
From the 1967 live satellite program "Our World" to MTV music videos in Indonesia, from French television in Senegal to the global syndication of African American sitcoms, and from representations of terrorism on German television to the international Teletubbies phenomenon, TV lies at the nexus of globalization and transnational culture. Planet TV provides an overview of the rapidly changing landscape of global television, combining previously published essays by pioneers of the study of television with new work by cutting-edge television scholars who refine and extend intellectual debates in the field. Organized thematically, the volume explores such issues as cultural imperialism, nationalism, postcolonialism, transnationalism, ethnicity and cultural hybridity. These themes are illuminated by concrete examples and case studies derived from empirical work on global television industries, programs, and audiences in diverse social, historical, and cultural contexts. Developing a new critical framework for exploring the political, economic, sociological and technological dimensions of television cultures, and countering the assumption that global television is merely a result of the current dominance of the West in world affairs, Planet TV demonstrates that the global dimensions of television were imagined into existence very early on in its contentious history. Parks and Kumar have assembled the critical moments in television's past in order to understand its present and future. Contributors include Ien Ang, Arjun Appadurai, Jose B. Capino, Michael Curtin, Jo Ellen Fair, John Fiske, Faye Ginsburg, R. Harindranath, Timothy Havens, Edward S. Herman, Michele Hilmes, Olaf Hoerschelmann, Shanti Kumar, Moya Luckett, Robert McChesney, Divya C. McMillin, Nicholas Mirzoeff, David Morley, Hamid Naficy, Lisa Parks, James Schwoch, John Sinclair, R. Anderson Sutton, Serra Tinic, John Tomlinson, and Mimi White.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé

De- Westernizing Media Theory to Make Room for African Experience - Nyamnjoh, Francis B. (Popular Media, Democracy and Development in Africa, 2010)
How should one think about popular media in the African context? Should we attempt to understand and analyse the increasing proliferation of tabloids, reality television shows, pop music, websites and mobile communications through the analytical frameworks constructed by scholars in the Global North, or does Africa pose unique research questions? Is there a danger of either essentializing Africa by treating her as ‘different’, or by ignoring her specificity by approaching her media via Western theoretical constructs? The scholar wishing to understand the interface between popular media, development and democracy in contemporary African societies is faced with a complex double bind. Elsewhere (Nyamnjoh 2005: 2-3) I have argued that African worldviews and cultural values are doubly excluded from global media discourses, first by the ideology of hierarchies and boundedness of cultures, and second by cultural industries more interested in profits than the promotion of creative diversity and cultural plurality. Little attention is accorded to how Africans negotiate and navigate the various identity margins and cultural influences in their lives, in ways that are not easily reducible to simple options or straightforward choices. The consequence of rigid dichotomies or stubborn prescriptiveness based on externally induced expectations of social transformation is an idea of democracy hardly informed by popular articulations of personhood and agency in Africa, and media whose professional values and content are not in tune with the expectations of those they purport to serve. The predicament of media practitioners in such a situation, as well as those wishing to understand African media practice through media theory, is obvious: to be of real service to liberal democracy and its expectations of modernity, they must ignore alternative ideas of personhood and agency in the cultural communities within which such practices take place and of which such practitioners and, often, scholars form part. Attending to the interests of particular cultural groups as strategically essential entities risks contradicting the principles of liberal democracy and its emphasis on civic citizenship and the autonomous individual, which media practitioners in African societies are being held accountable to.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

“Citizen Journalism” in the Syrian Uprising: Problematizing Western Narratives in a Local Context - Al-Ghazzi, Omar (Communication Theory, 2014)
This article analyzes the term ‘citizen journalism’ against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Décentrer l’histoire du jeu vidéo ? - Derfoufi, Mehdi (De l'autre côté, 2018)
Peut-on envisager une autre histoire du jeu vidéo ?
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Sexe, Race et Gaming - Derfoufi, Mehdi (Revue du Crieur, 2019)
Aucune étude n’a jamais démontré que les formes médiatiques disposeraient d’un pouvoir direct de transformation des réalités sociales. Une approche critique un peu sérieuse préférera ainsi appréhender le jeu vidéo comme le site d’un ensemble de rapports de pouvoir opérant au sein de la culture dominante, traversé, à l’instar d’autres formes culturelles, par des contradictions, des résistances et des réappropriations – autrement dit par des circulations dans la production de sens, les formes et les affects, qui viennent renforcer, nuancer ou déstabiliser les normes de l’hégémonie culturelle. Depuis le début des années 2010 et en particulier la polémique du #GamerGate en 2014, la communauté vidéoludique ne peut plus ignorer le sexisme. Les féministes n’ont pourtant pas attendu si longtemps pour se manifester. Mais c’est peut-être l’année 2012 qui marqua un réel tournant, lorsque Anita Sarkeesian lança une campagne de crowdfunding pour une série de vidéos sur sa chaîne YouTube feministfrequency. Sa démarche déclencha une vague de cyberharcèlement qui alla des insultes aux menaces de mort et jusqu’à la publication de données personnelles. Ce modèle de violence sexiste s’est reproduit à de multiples reprises, notamment en France en 2013 à l’encontre de la créatrice de jeu et féministe Mar_Lard, attaquée pour sa critique argumentée du sexisme dans la culture geek. Elle revenait en particulier sur des propos plus que complaisants d’un journaliste à propos d’une séquence où le personnage de Lara Croft, héroïne du mythique je…
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Racisme et jeu vidéo - Derfoufi, Mehdi (Éditions de la Maison des sciences de l'homme, 2021)
En 2007, le monde du jeu vidéo est secoué par une violente polémique au sujet du jeu vidéo Resident Evil 5. Ce dernier est accusé de faire commerce du racisme, en invitant à se glisser dans la peau d'un américain blanc body-buildé, missionné dans une région africaine anonyme, et tuant des dizaines d'hommes et de femmes noires présentées comme de dangereux zombies infectés du virus T. Depuis, la communauté des joueurs et joueuses de jeux vidéo interpelle régulièrement les créateurs et créatrices des jeux sur les questions du racisme et du sexisme.Dans son ouvrage, Mehdi Derfoufi analyse les rapports de force qui structurent l'industrie du jeu vidéo, dévoilant comment le racisme se niche parfois insidieusement au cœur de scénarios de jeux vidéo à succès. Il nous invite à nous questionner. Quels sont les pays qui pèsent sur les milliards d'euros du marché mondial du jeu vidéo ? Qui sont les game designers et auteurs des jeux ? Comment les représentations racistes sont-elles véhiculées à travers les personnageset les imaginaires vidéoludiques ? L'auteur nous dévoile avec brio les logiques racialisantes à l’œuvre au sein d’un marché économique très concurrentiel où des stéréotypes exotisants servent régulièrement à faire vendre un jeu. Il nous montre aussi comment la division internationale du travail et la hiérarchie économico-politique Nord/Sud pèse sur le marché du jeu vidéo et ralentit l’émergence de nouvelles représentations. Pourtant, de nombreux espoirs, notamment dans les pays du Sud participent au renouvellement de la culture geek : face aux violences racistes, la riposte s’organise.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Queer Korean Cinema, National Others, and Making of Queer Space in Stateless Things - Kim, Ungsan (Journal of Japanese & Korean Cinema, 2017)
Analyses the narrative and formal elements of Kim Kyung-mook's "Stateless things" (2011) to argue how it critiques South Korea’s ethnocentrism and homophobic social structures by delineating a queer use of space. Gives recent examples of homoeroticism in commercial and independent South Korean cinema. Argues that Kim's film expand the definition of queer Korean cinema by deconstructing and reconstructing the heteronormative, progress-driven cityscape of Seoul.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

De-Westernizing Film Studies - Ba, Saer Maty; Higbee, Will (Routledge, 2012)
De-Westernizing Film Studies aims to consider what form a challenge to the enduring vision of film as a medium - and film studies as a discipline - modelled on ‘Western’ ideologies, theoretical and historical frameworks, critical perspectives as well as institutional and artistic practices, might take today. The book combines a range of scholarly writing with critical reflection from filmmakers, artists & industry professionals, comprising experience and knowledge from a wide range of geographical areas, film cultures and (trans-)national perspectives. In their own ways, the contributors to this volume problematize a binary mode of thinking that continues to promote an idea of ‘the West and the rest’ in relation to questions of production, distribution, reception and representation within an artistic medium (cinema) that, as part of contemporary moving image culture, is more globalized and diversified than at any time in its history. In so doing, De-Westernizing Film Studies complicates and/or re-thinks how local, national and regional film cultures ‘connect’ globally, seeking polycentric, multi-directional, non-essentialized alternatives to Eurocentric theoretical and historical perspectives found in film as both an artistic medium and an academic field of study. The book combines a series of chapters considering a range of responses to the idea of 'de-westernizing' film studies with a series of in-depth interviews with filmmakers, scholars and critics. Contributors: Nathan Abrams, John Akomfrah, Saër Maty Bâ, Mohammed Bakrim, Olivier Barlet, Yifen Beus, Farida Benlyazid, Kuljit Bhamra, William Brown, Campbell, Jonnie Clementi-Smith, Shahab Esfandiary, Coco Fusco, Patti Gaal-Holmes, Edward George, Will Higbee, Katharina Lindner, Daniel Lindvall, Teddy E. Mattera, Sheila Petty, Anna Piva, Deborah Shaw, Rod Stoneman, Kate E. Taylor-Jones
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Décolonisant l'argent à Porto Rico - Negrón-Muntaner, Frances (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

L’art périphérique montre l’afro-diaspora en environnement digital - del Rei, Mariana (revue Periferias, 2021)
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

La conscience de la Mestiza. Vers une nouvelle conscience - Anzaldúa, Gloria (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2011)
Gloria Anzaldúa a délibérément écrit certains mots et certaines phrases en espagnol-chicano tout au long de cet article, choisissant pour des raisons politiques et esthétiques de produire un texte qui s’adresse à tout le monde mais peut être compris à des niveaux différents. Elle travaille ainsi aussi bien avec l’intelligibilité qu’avec la non-intelligibilité, liées au vécu et au positionnement social de chacun-e, au-delà de la langue elle-même. Pour tenter de respecter ce travail sur l’intelligibilité, nous avons procédé de la manière suivante. Dans certains cas, Anzaldúa a écrit une expression en espagno-chicano puis l’a traduite en anglais, nous avons alors procédé de la même manière. Dans les autres cas, nous avons laissé tel quel dans le corps du texte, ce qu’Anzaldúa a écrit en espagnol-chicano. Cependant, pour placer cette langue sur le même plan d’intelligibilité que l’anglais, pour le lectorat francophone, nous en proposons une traduction, en note. Enfin, nous avons ajouté un certain nombre de notes de contextualisation. Ainsi, les notes en lettres correspondent aux notes originales d’Anzaldúa, tandis que les notes en chiffres correspondent à la traduction de l’espagnol-chicano vers le français et enfin, les notes en i, ii, iii etc, correspondent aux notes des traductrices. Par ailleurs, deux termes sont particulièrement délicats à traduire : « raza » et « mestiza ». Au Mexique, le mot « raza » est polysémique. Au sens strict, il signifie « race », cependant son emploi actuel et courant n’implique aucune connotation raciale, mais plutôt populaire et affective (ma bande, mon quartier, ma famille élargie, les gens avec qui je m’identifie…), ce qui conduirait à le traduire plutôt par « peuple ». Nous avons donc choisi des traductions contextualisées, utilisant « race » pour la pensée de Vasconcelos (prise dans les courants racialistes internationaux des années vingt), et « peuple » pour la pensée d’Anzaldúa elle-même (qui l’utilise dans un sens actuel et populaire). L’ensemble de son œuvre montre amplement le caractère non-essentialiste de sa pensée, ce qui nous conforte dans ce choix. Enfin, le concept de « mestiza » (ou « mestizo ») possède au Mexique des connotations complexes et contradictoires. Il désigne une personne dominant-e par rapport à l’Indien-ne, mais aussi une personne dominé-e par rapport aux gens d’origine espagnole-européenne. Simultanément, il constitue l’archétype (positif) de la nouvelle « race » forgée dans l’ancienne colonie européenne transfigurée par l’indépendance puis la révolution. Pour Anzaldúa, le mot possède toutes ces connotations, mais signifie également la pluralité à l’intérieur de chaque être humain. Nous avons donc choisi de ne pas traduire le concept de « mestiza », qu’elle-même a décidé d’utiliser en espagnol, son article visant précisément à expliquer le sens nouveau qu’elle donne à la « nouvelle métisse ».
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Queering Decolonization – Two Spirit Resistance Across Borders From Turtle Island to Palestine (2019)
Avec Alex Wilson, Jeffrey McNeil, Teddy Syrette, May Ela and Ahmed Maswadeh.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Charla | Estética afro Identidad, saberes y resistencia - Banrepcultural (2019)
En esta charla conversaremos sobre las luchas históricas por la reivindicación de los derechos del pueblo afro que están detrás de su estética, específicamente en dos de sus expresiones femeninas: el turbante afro y el pelo natural, los cuales han servido como elementos de resistencia para la pervivencia de las prácticas y costumbres ancestrales. Como parte de la exposición temporal del Museo del Oro 'A bordo de un navío esclavista, La Marie-Séraphique' (que se presentó en Bogotá del 7 de octubre de 2018 al 7 de abril de 2019) hablamos en el museo sobre algunos peinados ancestrales, como la espina de pescado, las tropas, el hundidito, el ciempiés y la vicha, y sobre los usos, significados y modelos de los turbantes afro, como la cadena del esclavo, la autoridad, el kitambala, el enkeycha y el doek. El termino mata ‘e pelo surge de las expresiones propias de nuestras ancestras, que se referían al pelo afro cómo una gran mata (árbol), frondosa, incontrolable y rizada, que requería unos cuidados particulares por su condición crespa, abundante y diversa. El cuerpo de la mujer negra, raizal y palenquera ha estado históricamente ligado a las luchas por la reivindicación de los derechos del pueblo afro, siendo la mata ‘e pelo el elemento estético que más las ha transmitido. Entre las personas de ancestros africanos, la estética del pelo afro se remonta a un pasado cargado de lucha y resistencia, pues las trenzas fueron usadas para la elaboración de mapas que marcaban el camino a la libertad de los cimarrones. Las mujeres se reunían en el patio para peinar a las más pequeñas. Diseñaban en su cabeza un mapa lleno de caminitos y salidas de escape, en el que ubicaban los montes, ríos y árboles más altos. Así, al verlas, los hombres sabían cuáles rutas tomar. Su código, desconocido para los amos, les permitía a los esclavizados huir. El balance humano de la trata de cautivos africanos a través del Atlántico es dramático: con una inmensa brutalidad, desplazó a 13 millones de hombres, mujeres y niños entre la segunda mitad del siglo XVI y finales del siglo XIX. #ElMuseoDelOroTambiénEsAfro Producción Banco de la República Realización Santiago Martínez
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Presencia negra en Bogotá: Décadas 1940-1950-1960
La exposición Presencia negra en Bogotá hace parte de la investigación en Migraciones que desde la Universidad Nacional lideran Mercedes Angola y Maguemati Wabgou. Está presente en el Claustro de San Agustín, como un homenaje a los hacedores de grandes historias que se desconocen, personas cuyos aportes a la construcción de la sociedad colombiana y a la consolidación de la identidad nacional desde diversas perspectivas y disciplinas ha invisibilizado la historia colombiana. En compañía de sus protagonistas, acompáñenos en la formulación de nuevas preguntas de investigación en torno al aporte de la gente negra a Colombia y a países vecinos, pues no solo se ha producido migración interna sino, "fuga" hacia otros países. Invitados : Mercedes Angola, artista plástica e investigadora y Maguemati Wabgou, sociólogo e investigador.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

¡Mandinga sea! África en Antioquia - Luz Adriana Maya Restrepo; Raúl Cristancho (Universidad de los Andes, 2015)
Compuesta por 355 obras de arte de naturaleza muy variada, la exposición en sala y ahora impresa busca visibilizar, dignificar, valorar y difundir los legados civilizatorios, reativos, culturales, económicos, sociales, políticos, tecnológicos, ambientales e históricos de los pueblos del África occidental y de sus descendientes en la construcción de Antioquia. Además, este catálogo pretende ubicar en las manos del público, y de los especialistas en museos y en estética, el de-bate sobre las encrucijadas que encierra la representación museal de las obras artísticas y de las culturas de los pueblos afroamericanos fraguados en el seno de las dinámicas esclavistas, imperiales y coloniales.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Postcolonial Modernism: Art and Decolonization in Twentieth-Century Nigeria - Okeke-Agulu, Chika (Duke University Press, 2015)
Written by one of the foremost scholars of African art and featuring more than 125 color images, Postcolonial Modernism chronicles the emergence of artistic modernism in Nigeria in the heady years surrounding political independence in 1960.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Lyrical Nationalism: Gender, Friendship, and Excess in 1970s Hindi Cinema - Jha, Priya (The Velvet Light Trap, 2003)
In this essay I examine one particular feature of the films, the song-and-dance sequences, as they draw attention to the fractious nature of the postcolonial nation while simultaneously attempting to construct a space for the articulation of a consolidated national identity.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Multiculturalismo y crítica postcolonial: la diáspora artística latinoamericana (1990-2005) - Marín Hernández, Elizabeth (Universitat de Barcelona, 2005)
La presencia del arte contemporáneo latinoamericano en el mundo contemporáneo, es concebida y movilizada a través de la existencia de una diáspora que ha perdido toda clase de arraigo en sus lugares territoriales definitorios. Los lenguajes que éstas muestran tienden ha consolidar un gusto por la simultaneidad, por la complejidad, por lo marginal, por lo oculto, y por las relativizaciones de una realidad que se pregunta constantemente por el sentido de su ser. Las diásporas artísticas ubican sus propuestas en medio de una serie de posicionamientos, para tratar de narrar las historias y las situaciones, que comenzaron ha emerger, en el momento en el cual se establece una dominante epocal, observadora y tolerante de la diversidad de los márgenes. El arte de las diásporas parecía configurar un nuevo espacio de representación, digno de ser atrapado o explicado dentro de nuevas posiciones teóricas, que manifestarán el por qué de unas de estas expresiones, muchas veces imposibles de traducir ante la pérdida del sentido del monopolio cultural occidental en el campo de las artes. De allí que, se hallan confeccionado en el mundo contemporáneo tardocapitalista y posindustrial, posiciones teóricas que incluyentes y estudiosas de la alteridad, de las diferencias, de la otredad, de la subalternidad. Para partir de los enunciados fragmentarios y múltiples mostrados por las teorías multiculturalistas y por la Crítica Poscolonial. Un intento de dotar de sentido a una realidad global, que ha perdido las fronteras. En este sentido, el espectro teórico que estudia a la diversidad observa a las culturas, a sus contaminaciones y desplazamientos desde diversas perspectivas, las cuales han incido en el mundo del arte contemporáneo en la formulación de un Nuevo Internacionalismo incluyente de las representaciones de los otros. El arte latinoamericano en este contexto se encuentra convocado, invitado, para legitimar la puesta en escena de unas realidades que pretenden ser cercanas, y a su vez alejadas, por las tensiones producidas por las propuestas discursivas del multiculturalismo y del poscolonialismo, en sus lecturas sobre las culturas como opuestas y no como parte integrante de una metacultura global. Las diásporas se ubican a partir de la deconstrucción de los postulados mayores de estas nuevas tendencias teóricas, para evidenciar su localidad desde la particularidad de sus legados e historias. Espacio en el cual, los artistas pertenecientes a la diáspora contemporánea, han demostrado responder con presteza a la cantidad de situaciones presentadas en medio de una realidad interconectada desde tiempos anteriores, y que en la actualidad manifiesta la exacerbación de las relaciones con lo que se pretende diferente.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Writing Art Histories From Below: A Decolonial Guanaca-Hood Perspective - Cornejo, Kency (Latin American and Latinx Visual Culture, 2019)
As a teenager during my first internship at the Los Angeles County Museum of Art, a diversity initiative for inner-city youth, the education curator enthusiastically asked, “Who here would like to be an art historian!?” Like all the other Black and Brown inner-city kids, I laughed inside. My response was not due to a lack of art appreciation; I grew up in a family of refugees who were all self-taught artists back home in El Salvador, who taught me to draw before I learned to read. Nor was my response rooted in apathy for creative expression, for I was involved in art and theater from my elementary through my high school years. Art was such a natural part of my life that the idea of studying it seemed wasteful to me. The truth was, the internship was one of two jobs I was working to financially help my family and pay for my first year of community college. Hidden even deeper, though, I believed the museum world was not my world. I was a guanaca (the appellative given to people from El Salvador) whose family fled war and remained invisible in mainstream US Latinx history and culture. I was also from the hood—in my case Compton, California, a city made notorious by gangsta rap and police brutality. I believed that people like me guarded the art on the museum walls, cleaned the floors and bathrooms for visitors, and served the food at the high-priced café. People who looked like me, who came from where I did, did not determine what art could be, nor could we afford to buy it. We certainly did not write the history of art, for if we had, we would see ourselves represented on the walls.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé